An Adaptive Clustering Scheme for Improving the Scalability in Intelligent Transportation Systems - Yen-Wen Lin; Hao-Chun Weng; Tsung-Han Lee; Shan-Yin Hou (International Journal of Distributed Sensor Networks)
Intelligent Transportation Systems (ITSs) aim at making the vehicle users be safer, comfortable, and better informed. Internet-enabled ITS applications get increasingly attractive recently. In this context, gateway is the portal of accessing the Internet. The efficiency of gateway management in ITSs thus profoundly affects the applicability of Internet-enabled applications. When the number of vehicles on the road greatly increased, the effectiveness of gateway requisition challenges the usage of the ITS services. To remedy the scalability problem in accessing the Internet in ITSs, an adaptive clustering scheme for gateway management is proposed in this paper. In the proposed scheme, the gateways are organized as a two-level cluster architecture. The gateways are dynamically employed according to the QoS requirements of the applications and current networking conditions. As shown in the simulation results, the proposed scheme is able to achieve the QoS requirements with fair gateway deployment cost.